Baseline lung function and risk of incident tuberculosis: a nationwide population-based cohort study - Kyu Yean Kim; Yong-Moon Park; Seung Hyun Ko; Kyungdo Han; Seung Hoon Kim; Shin Young Kim; Sung Kyoung Kim (PLoS ONE, 2025)
Background While lung function is known to decrease after suffering from pulmonary tuberculosis (TB), little is known about whether baseline lung function is associated with the occurrence of TB in the general population. This study aimed to evaluate the risk of incident TB according to baseline lung function. Methods A nationwide population-based cohort study was conducted using a database derived by cross-referencing Korea National Health and Nutrition Examination Survey and National Health Insurance Service between 2010 and 2016. Of 29,524 subjects, 16,594 participants aged over 40 years who had spirometry results without a previous TB history were enrolled. The primary endpoint was newly developed TB. Results Among 16,457 participants, 72 were newly diagnosed with TB during the follow-up period (median: 5.5 years). TB risk was higher in participants with obstructive lung function impairment (aHR: 2.033, 95% CI: 1.123–3.679) or restrictive lung function impairment (aHR: 2.193, 95% CI: 1.120–4.294) than in those with normal lung function. Low forced expiratory volume in one second (FEV1) was associated with increased TB risk (aHR [lowest quartile vs. highest quartile]: 1.91, 95% CI: 1.05–3.50; aHR [lowest decile vs. highest decile]: 2.76, 95% CI: 1.14–6.70; both p for trends < 0.0001). Conclusion Our findings suggest that impaired lung function might increase TB risk and that TB risk might be inversely associated with FEV1.